2023
DOI: 10.35542/osf.io/fnh48
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Will ChatGPT get you caught? Rethinking of Plagiarism Detection

Abstract: The rise of Artificial Intelligence (AI) technology and its impact on education has been a topic of growing concern in recent years. The new generation AI systems such as chatbots have become more accessible on the Internet and stronger in terms of capabilities. The use of chatbots, particularly ChatGPT, for generating academic essays at schools and colleges has sparked fears among scholars. This study aims to explore the originality of contents produced by one of the most popular AI chatbots, ChatGPT. To this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0
10

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(67 citation statements)
references
References 11 publications
2
55
0
10
Order By: Relevance
“…This problem makes ChatGPT generated text unsuitable for academic writing (García-Peñalvo, 2023). Issues of plagiarism detection in write-ups generated by ChatGPT have been raised, as well as how to distinguish between fact and fiction text generated (Chatterjee & Dethlefs, 2023;Khalil & Er, 2023). Instructors are increasingly worried that students may use ChatGPT to produce their written assignments, as it has been demonstrated to generate reports in a matter of seconds without being detected by plagiarism detectors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem makes ChatGPT generated text unsuitable for academic writing (García-Peñalvo, 2023). Issues of plagiarism detection in write-ups generated by ChatGPT have been raised, as well as how to distinguish between fact and fiction text generated (Chatterjee & Dethlefs, 2023;Khalil & Er, 2023). Instructors are increasingly worried that students may use ChatGPT to produce their written assignments, as it has been demonstrated to generate reports in a matter of seconds without being detected by plagiarism detectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, when using GPT-3, authors or students should make it clear that the model was used and cite or reference it appropriately. Khalil and Er (2023) conducted an experiment to determine whether plagiarism detection tools could detect essays written using ChatGPT, and found that of the 50 essays tested, 40 had a similarity score of 20% or less, demonstrating a high degree of originality. Similarly, Susnjak (2022) used ChatGPT in an experiment to assess its ability to engage in critical thinking rather than simply information retrieval, and the results were highly accurate and precise, as well as logically coherent.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Adicionalmente, destaca como elemento a tener en cuenta, la poca capacidad que tienen los docentes para identificar trabajos con intervención de las IA, a pesar de que en la institución existe la herramienta Turnitin y los profesores están capacitados para utilizarla con eficiencia. Esto concuerda con investigaciones recientes en las que se muestra una reducida eficacia de esta herramienta para detectar los trabajos creados por IAs (Diaz-Arce, 2023; Khalil & Er, 2023;Perkins, 2023;Rudolph et al, 2023). Por ello se resalta la necesidad de insistir no solo en ampliar las políticas internas sobre probidad académica para que incluyan el Plagio IA (plagio a herramientas IA) dentro de sus prohibiciones, sino también en soluciones más integrales y preventivas pues es un problema que puede extenderse rápidamente.…”
Section: Discussionunclassified
“…De este modo, no solo puede recibir instrucciones y ejecutarlas, sino que también la procesa para aprender y mejorar su desempeño respecto a la actividad para la que fue creada (Incio-Flores et al, 2021). Sin dudas, se refiere a un avance tecnológico que puede significar un salto cualitativo y cuantitativo significativo en múltiples aspectos de la sociedad, pero que muchos tienen fundadas preocupaciones respecto al mal uso que se les pueda dar en el ámbito educativo y profesional (Arif et al, 2023;Cotton et al, 2023;Guo et al, 2023;Khalil & Er, 2023;Macdonald et al, 2023;Perkins, 2023;Rudolph et al, 2023;Susnjak, 2022).…”
Section: Introductionunclassified